Companion of the 2020 ACM/IEEE International Conference on Human-Robot Interaction 2020
DOI: 10.1145/3371382.3378348
|View full text |Cite
|
Sign up to set email alerts
|

Robot Morphology and Children's Perception of Social Robots

Abstract: The aim of this study was to investigate whether robot morphology (i.e., anthropomorphic, zoomorphic, or caricatured) influences children's perceptions of animacy, anthropomorphism, social presence, and perceived similarity. Based on a sample of 35 children aged seven to fourteen, we found that, depending on the robot's morphology, children's perceptions of anthropomorphism, social presence, and perceived similarity varied, with the anthropomorphic robot typically ranking higher than the zoomorphic robot. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Furthermore, robots' morphologies significantly affect how children perceive robots. The study found that people's perception of robots is related to the levels of anthropomorphism and social presence that the robots convey [Barco et al 2020]. Interestingly, children relate to anthropomorphic robots with a higher level of intimacy compared with zoomorphic robots.…”
Section: Safety Requirements For Bystanders and Pedestriansmentioning
confidence: 90%
“…Furthermore, robots' morphologies significantly affect how children perceive robots. The study found that people's perception of robots is related to the levels of anthropomorphism and social presence that the robots convey [Barco et al 2020]. Interestingly, children relate to anthropomorphic robots with a higher level of intimacy compared with zoomorphic robots.…”
Section: Safety Requirements For Bystanders and Pedestriansmentioning
confidence: 90%
“…Research indicates that perceptions of observable robot characteristics do influence judgments regarding robots' mental capacities. For instance, Barco et al (2020) and Hegel et al (2008) demonstrated that robots with a humanlike form are more anthropomorphized than functional and zoomorphic robots. Moreover, the perception that a nonhuman target moves at a speed similar to the speed of human movement has been shown to increase mind attribution (Morewedge et al, 2007).…”
Section: Precursors and Consequences Of Anthropomorphismmentioning
confidence: 99%
“…Unidimensional conceptualizations of anthropomorphism are frequently employed (Barco et al, 2020;Bartneck et al, 2009;Salem et al, 2013), the most prominent being the conceptualization by Bartneck and colleagues (2009). Unidimensional conceptualizations are not per se problematic if they are rooted in an accurate theoretical definition.…”
Section: Uni-versus Multidimensional Conceptualizations Of Anthropomo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only recently have efforts at digital literacy begun to explore AI/algorithmic literacy [49]. However, such efforts were still mainly focused on broader concepts, such as social robotics [9,41], AI [58] and machine intelligence [22]. Children's perceptions of agents powered by AI algorithms have been shown to be strongly influenced by their previous interactions with them [80].…”
Section: Children's Perceptions Of Datafication Onlinementioning
confidence: 99%